Membangun Loyalitas Pelanggan melalui Harga dan Kepercayaan dengan Kepuasan Pelanggan sebagai Variabel Mediasi pada Bisnis Smartphone - Emil Salim; Andri Andri; Mondra Neldi (Fakultas Ekonomi Universitas Islam 45, 2019)
Nowadays in the globalization era, particularry in Indonesia, the dense population is accompanied byincreasingly complex needs and various human activities in carrying out mobility whether doingwork, school, tourism, research or traveling. Thus, smartphone enhancements to accessories becomeone of the important daily needs. This situation eventually led to increasingly fierce competitionbetween outlets and companies that manufacture, distribute, and sell smartphone devices oraccessories in the existence of competing companies providing the best service to attract consumers.This study aims to build customer loyalty through price and trust using mediating variables, namelycustomer satisfaction. The research method used in this study is a quantitative method with a sampleof 85 respondents. Data analysis method used multiple linear regression analysis and path analysiswith the application of Statistical Package for Social Sciences (SPSS 21.00). The study result showedthere is an indirect relationship smaller in value than a direct relationship, meaning that loyalty doesnot mediate the relationship between price and customer satisfaction and indirect relationships are lessvaluable than a direct relationship, meaning loyalty does not mediate the relationship of trust withcustomer satisfaction